ANALISIS PERBANDINGAN KINERJA KEUANGAN DAN ABNORMAL RETURN SEBELUM DAN SESUDAH AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Harry Adityawan (2023)
The objective of this study is to examine the differences in financial performance and abnormal return of companies before and after acquisition in companies listed on the Indonesia Stock Exchange during the period of 2019-2021. The sample size used in this research is 18 companies selected through purposive sampling approach. The analysis techniques employed are the Wilcoxon Signed-Rank Test and the Paired Sample t-Test. Liquidity, solvency, profitability, and abnormal return are used as variables in this study. The findings of this research indicate that there are no significant differences in the current ratio, debt to equity ratio, return on equity, and abnormal return of companies before and after the acquisition. Keywords : Liquidity, Solvency, Profitbality, Abnormal Return, Acquisitons